A Weak Response to Endoplasmic Reticulum Stress Is Associated With Postoperative Organ Failure in Patients Undergoing Cardiac Surgery With Cardiopulmonary Bypass - Clavier, Thomas; Demailly, Zoé; Semaille, Xavier; Thill, Caroline; Selim, Jean; Veber, Benoit; Doguet, Fabien; Richard, Vincent; Besnier, Emmanuel; Tamion, Fabienne (Frontiers in Medicine, 2021)
Introduction: Endoplasmic reticulum stress (ERS) is involved in inflammatory organ failure. Our objective was to describe ERS, its unfolded protein response (UPR) expression/kinetics during cardiac surgery with cardiopulmonary bypass (CPB) and its association with postoperative organ failure (OF). Methods: Prospective study conducted on patients undergoing cardiac surgery with CPB. Blood samples were taken before (Pre-CPB), 2h (H2-CPB) and 24h (H24-CPB) after CPB. Plasma levels of 78 kDa Glucose- Regulated Protein (GRP78, final effector of UPR) were evaluated by ELISA. The expression of genes coding for key elements of UPR (ATF6, ATF4, sXBP1, CHOP) was evaluated by quantitative PCR performed on total blood. OF was defined as invasive mechanical ventilation and/or acute kidney injury and/or hemodynamic failure requiring catecholamines. Results: We included 46 patients, GRP78 was decreased at H2-CPB (1328[878-1730]ng/ml vs. 2348[1655-3730]ng/ml Pre-CPB; p<0.001) but returned to basal levels at H24-CPB (2068[1436-3005]ng/ml). The genes involved in UPR had increased expression at H2 and H24. GRP78 plasma levels in patients with OF at H24-CPB (n=10) remained below Pre-CPB levels (-27.6[-51.5;-24.2]%) compared to patients without OF (n=36) in whom GRP78 levels returned to basal levels (0.6[-28.1;26.6]%; p<0.01). H24-CPB ATF6 and CHOP expressions were lower in patients with OF than in patients without OF (2.3[1.3-3.1] vs. 3.0[2.7-3.7], p<0.05 and 1.3[0.9-2.0] vs. 2.2[1.7-2.9], p<0.05, respectively). Conclusions: Low relative levels of GRP78 and weak UPR gene expression appeared associated with postoperative OF. Further studies are needed to understand ERS implication during acute organ failure in humans.